Exercise right heart catheterisation before and after pulmonary endarterectomy in patients with chronic thromboembolic disease. Issue 3 (17th September 2018) - Guth, Stefan; Wiedenroth, Christoph B.; Rieth, Andreas; Richter, Manuel J.; Gruenig, Ekkehard; Ghofrani, Hossein Ardeshir; Arlt, Matthias; Liebetrau, Christoph; Prüfer, Diethard; Rolf, Andreas; Hamm, Christian W.; Mayer, Eckhard
Symptomatic patients with chronic thromboembolic disease (CTED) without pulmonary hypertension often show an excessive increase in mean pulmonary arterial pressure (MPAP) during exercise. We report on the impact of pulmonary endarterectomy (PEA) on pulmonary haemodynamics in a prospective series of 32 consecutive CTED patients who underwent PEA. All patients had a comprehensive diagnostic work-up including right heart catheterisation at baseline and 12 months after PEA. Furthermore, in 12 patients exercise right heart catheterisation was performed before and after PEA. After PEA, MPAP was lower at rest (20±3 versus 17±3 mmHg; p=0.008) and during maximal exercise (39±8 versus 31±6 mmHg; p=0.016). The mean total pulmonary resistance (TPR) decreased from 3.6±0.8 Wood Units (WU) pre-operatively to 2.7±0.7 WU 1 year after PEA (p=0.004) and the mean slope of the MPAP/cardiac output (CO) relationship decreased from 3.6±1.0 to 2.3±0.8 WU (p=0.002). Peak oxygen uptake increased from 1.2±0.4 to 1.5±0.3 L·min −1 (p=0.014) and ventilatory equivalents of carbon dioxide decreased from 39±2 to 30±2 (p=0.002). There was a significant improvement in quality of life assessed by the Cambridge Pulmonary Hypertension Outcome Review questionnaire. In CTED patients, PEA resulted in haemodynamic and clinical improvements. The means of TPR and MPAP/CO slopes decreased to <3.0 WU. Pulmonary endarterectomy reduces means of TPR and MPAP/CO slopes to <3.0 Wood Units in patients with chronic thromboembolic disease http://ow.ly/Jw4z30lbefW